The Environment as a Stakeholder? A Fairness-Based Approach - Phillips, Robert A. (Journal of business ethics, 2000)
Stakeholder theory is often unable to distinguish those individuals and groups that are stakeholders from those that are not. This problem of stakeholder identity has recently been addressed by linking stakeholder theory to a Rawlsian principle of fairness. To illustrate, the question of stakeholder status for the non-human environment is discussed. This essay criticizes a past attempt to ascribe stakeholder status to the non-human environment, which utilized a broad definition of the term "stakeholder." This paper then demonstrates how, despite the denial of stakeholder status, the environment is nonetheless accounted for on a fairness-based approach through legitimate organizational stakeholders. In addition, since stakeholder theory has never claimed to be a comprehensive ethical scheme, it is argued that sound reasons might exist for managers to consider their organization's impact on the environment that are not stakeholder-related.